Prevalence and clinical impact of cachexia in chronic illness in Europe, USA, and Japan: facts and numbers update 2016. Issue 5 (2nd November 2016) - von Haehling, Stephan; Anker, Markus S.; Anker, Stefan D.
Abstract: Cachexia is a serious clinical consequence of almost all chronic diseases when reaching advanced stages. Its prevalence ranges from 5–15% in end‐stage chronic heart failure to 50–80% in advanced malignant cancer. Cachexia is also frequently occurring in patients with chronic kidney disease, chronic obstructive pulmonary disease (COPD) or neurological diseases, and rheumatoid arthritis. Mortality rates of patients with cachexia range from 15–25% per year in severe COPD through 20–40% per year in patients with chronic heart failure or chronic kidney disease to 20–80% in cancer cachexia. In the industrialized world (North America, Europe, and Japan) where epidemiological data are to some degree available, the overall prevalence of cachexia (due to any disease and not necessarily associated with hospital admission) is growing with the growth of the chronic illness prevalence, and it currently affects around 0.5–1.0% of the population, i.e. around 6–12 million people. From this, one can estimate that 1.5–2 million deaths are occurring in patients with cachexia per year. It is also a very significant health problem in other parts of the globe, but epidemiological data are scarce. The multifactorial nature of cachexia is now much better understood, and particularly, the role of inflammatory mediators and the imbalance of anabolism and catabolism are considered important therapeutic targets. Several approaches to develop cachexia and muscle wasting treatments have failed to be successful in phase III clinical trials, but new approaches are in development. Given the high prevalence and very high mortality associated with cachexia, advances are urgently needed for patients worldwide.